Ownership structure and voluntary disclosure in Malaysian listed firms - Ho, Poh-Ling (Groupe Ecole Supérieure de Commerce (ESC) Dijon-Bourgogne., 2008)
This study investigates the impact of ownership structure on the extent of voluntary disclosure by Malaysian listed firms over the volatile time period 1996 to 2006. During this period of time, the onset of the 1997 Asian financial crisis and global corporate scandals resulted in major institutional and environmental changes. The nature of these regulatory reforms clearly impacted on firm management's incentives to voluntarily disclose more information in annual reports.The results show that the average level of voluntary disclosure is generally low although there is an increase in the extent of voluntary disclosure exhibited by Malaysian firms over the eleven-year time period. Controlling for firm size, leverage and profitability, the empirical results show that ownership concentration is positively associated with voluntary disclosure. The positive association of high ownership concentration may reflect the firms' choice to disclose more information as a governance initiative to enhance transparency. Institutional and foreign ownership have motivation to disclose in excess of mandatory requirements. The findings imply that the presence of institutional and foreign investors in a firm pushes firms to voluntarily disclose more information in annual reports. Such enhanced disclosure practice should be encouraged in order to attract funds from such investors both locally and abroad.